Sendratari Mayo Shidiq Sebagai Sarana Alternatif Pembelajaran Moral (Analisis Fenomenologis) - Rohmah, Ichmi Yani Arinda (LoroNG: Media Pengkajian Sosial Budaya, 2014)
Tari Mayo Shidiq is a traditional art coming from Bojonegoro, East Java. This art includes new art which modifies traditional art with modern art. In practice, the art of Tari Mayo Sidiq is not used as entertainers an sich but also used as an alternative way of moral learning (responsibility) in SDN Jatigede, Bojonegoro. Results obtained from studies conducted that Tari Mayo Shidiq is relevant if it is used as a learning tool to understand and train students to have an attitude of responsibility. It is as the result of the assessment by teachers and other school students who take Tari Mayo Sidhiq extracurricular. bangsa Indonesia. Sejatinya pendidikan pesantren yang tetap mempertahankan kurikulum mandirinya tetap menjadi pilihan, tanpa tergeser sedikitpun meskipun dunia semakin modern dan memasuki era globalisasi. Pendidikan pesantren sebagai pendidikan yang berbasis nilai (value oriented) menjadi satu-satunya pendidikan alternatif yang mampu membentuk jati diri manusia. Pendidikan karakter masuk menjadi fokus utama dalam membentuk manusia seutuhnya. Melalui pesantren inilah dirasa mampu mewujudkan manusia seutuhnya dengan peng-internalisasian nilai yang dengan sengaja ditanamkan.